Revision of the polyphyletic genus Hirrius Bolívar, 1887 (Orthoptera: Tetrigidae), with descriptions of three new genera and insights into antennal sensilla morphology - Skejo, Josip; Husemann, Martin; Jr., Romeo Patano; Tumbrinck, Josef; Pushkar, Taras I.; Pavlović, Marko; Mohagan, Alma; Pamin, Jan-Henrik; Kasalo, Niko (Zootaxa, 2024)
Discotettiginae were recently synonymized with Scelimeninae, but the polyphyletic genus Hirrius Bolívar, 1887, with five species endemic to the Philippines and Sulawesi, remained an unsolved issue. Besides similarly widened subapical antennomeres, head and pronotum, other traits suggest that Hirrius members belong to different subfamilies. The genus is now split into four genera, with four new species. Hirrius (Tetrigidae: incertae sedis) now includes three species, one of which is new, all endemic to Mindanao, the Philippines: H. punctatus (Stål 1877), H. mindanaensis (Günther, 1938), and H. ruber Skejo, Patano et Kasalo sp. nov. A lectotype is designated for H. punctatus, because the type series was found to contain two different species belonging to two different genera. Three new genera are described. Genus Parahirrius Skejo, Patano et Kasalo gen. nov. (Tetrigidae: incertae sedis) consists of P. parvus Skejo, Patano et Kasalo sp. nov. and P. amorosus Skejo, Patano et Kasalo sp. nov., both endemic to Mindanao. Genus Zvierckia Skejo, Tumbrinck et Pushkar gen. nov. (Scelimeninae: Discotettigini) includes Z. montana (Günther, 1937), comb. nov., Z. sarasinorum (Günther, 1937), comb nov., and Z. storozhenkoi Skejo et Tumbrinck sp. nov., all endemic to Sulawesi. Genus Guentheracris Skejo, Tumbrinck et Pushkar gen. nov. (Tetrigidae: “Asian Metrodorinae”) includes G. scrobiculata (Günther, 1937), comb. nov. from Sulawesi. Subapical antennomeres of Zvierckia storozhenkoi sp. nov. and Phaesticus mellerborgi (Stål, 1855) were scanned for the first time and compared to Discotettix belzebuth (Serville, 1838). Zvierckia gen. nov. and Discotettix Costa, 1864, both Scelimeninae: Discotettigini members, share many features of the antennal morphology, such as many basiconic sensilla on the antennal margins giving the ridge a saw-like impression. On the other hand, antennae of Phaesticus Uvarov, 1940 contain many elongated placoid sensilla, which are fully absent in the subapical widened segments of Zvierckia gen. nov. and Discotettix.